2018
DOI: 10.1111/jgh.14540
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endoscopic ultrasound tissue acquisition methods for genomic analysis of pancreatic cancer

Abstract: Background and Aim Tumor genotyping may allow for improved prognostication and targeted therapy for pancreatic ductal adenocarcinoma (PDAC). We aimed to compare endoscopic ultrasonography (EUS) with fine needle aspiration (FNA) to fine needle biopsy (FNB) for obtaining sufficient tissue for genomic analysis and theranostic potential. Methods A retrospective cohort study of patients that underwent EUS‐FNA or EUS‐FNB with either positive or suspicious cytology for PDAC between March 2016 and December 2017. Demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 17 publications
2
91
1
Order By: Relevance
“…No prospective trials have evaluated the adequacy of EUS-TA samples for NGS, but several retrospective studies have reported that the adequacy of EUS-TA samples for NGS ranged from 60% to 100% [78,79,80,81] (Table 1).…”
Section: Clinical Utility Of Eus-ta For Ngsmentioning
confidence: 99%
“…No prospective trials have evaluated the adequacy of EUS-TA samples for NGS, but several retrospective studies have reported that the adequacy of EUS-TA samples for NGS ranged from 60% to 100% [78,79,80,81] (Table 1).…”
Section: Clinical Utility Of Eus-ta For Ngsmentioning
confidence: 99%
“…However, several studies have shown that FNB is associated with better results compared to FNA in several types of pancreatic lesions. Elhanafi et al showed that FNB should be considered when pancreatic adenocarcinoma genotyping is requested, especially for tumors smaller than 3 cm located in the head/neck of the pancreas [34]. In a retrospective study including 91 patients over a 13-year period evaluating FNA and FNB in neuroendocrine pancreatic tumors, FNB was found to improve diagnostic sensitivity and conferred additional information to cytological assessment [35].…”
Section: Resultsmentioning
confidence: 99%
“…Larson et al observed no difference between the two needle types,[ 77 ] but in a larger trial by Elhanafi et al including 167 patients, the proportion of samples sufficient for NGS was higher in the FNB group. [ 78 ] However, both the abovementioned studies are retrospective in design, and prospective comparative studies are lacking.…”
Section: Novel Applications and Future Aspectsmentioning
confidence: 99%